Impact of compensation, Leadership, and Discipline on Employee Performance - Anita, Ifa Fitri; Turmudhi, Anis (Asean International Journal of Business, 2025)
This study aims to identify factors that affect the performance of MSME employees of Kripik Tahu Walik Cemara Kembar Magelang City Regency. This study tests 3 (three) hypotheses, namely: The following factors affect employee performance: compensation, leadership, and work discipline. The location of the survey was MSMEs Tahu Walik Chips. The data of this study was collected through a questionnaire from 53 employees. The method for analyzing data uses the classic hypothesis test, Multiple linear regression. The study results show that compensation, leadership, and work discipline improve employee performance. Based on the study's results, it is proposed that managers need to participate in decision-making so that employees can succeed. More attention must be paid to salary offers, allowances, and facilities, which need improvement. Performance should be improved by prioritizing attendance, Discipline, and achieving goals.